Control Plane Issues in the 4WARD Network Virtualization Architecture - Bless, Roland; Werle, Christoph (Electronic Communications of the EASST, 2009)
Network virtualization technologies offer a lot of opportunities and advantagesbut create also new issues that need to be solved. In this paper, we discusscontrol mechanisms, interfaces, and protocols required in order to allow for dynamicsetup of virtual networks. Finally, we describe some runtime aspects by examiningcontrol interfaces and signaling protocols necessary for the management of virtualnetworks.